Against all odds—late repair of multiple shunt lesions in a patient with Down syndrome: a case report. Issue 7 (18th July 2021) - Arvanitaki, Alexandra; Januszewska, Katarzyna; Malec, Edward; Baumgartner, Helmut; Kehl, Hans-Gerd; Lammers, Astrid Elisabeth
Abstract: Background: Children with congenital heart defects (CHD) usually undergo elective surgical repair of haemodynamically relevant shunt lesions within the first year of life. Due to susceptibility for pulmonary arterial hypertension (PAH) in patients with Down syndrome, repair is usually aimed for no later than 6 months of life. However, with rising immigration from developing countries to Europe, more patients with unrepaired CHD are diagnosed at a later age. Anatomical repair may be precluded, when advanced pulmonary vascular disease has been established. Case summary: We report a 39-month-old male patient with Down syndrome with a large non-restrictive perimembranous ventricular septal defect, a large patent ductus arteriosus, and a secundum-type atrial septal defect with a prominent left-to-right shunting. Haemodynamic assessment revealed only a mild increase of pulmonary artery pressures (mPAP) with low pulmonary vascular resistance index (PVRi). Vasodilator testing led to a further increase of the left-to-right shunt and decrease of PVRi, suggesting operability. After careful consideration, the patient underwent complete surgical repair with a good post-operative clinical outcome. Cardiac catheterization 6 months after corrective repair showed a normal mPAP. No signs of PAH have been detected in the medium-term follow-up. Discussion: Expertise, increased physician awareness, and a thorough pre-operative multidisciplinary evaluation are paramount to determine the best treatment approach for patients, who may present late with multiple shunts, and—in our case—underlying Down syndrome. Long-term close post-surgical follow-up in an expert centre is warranted to promptly diagnose and treat a possible late presentation of PAH appropriately.